Atypical penetrating laryngeal trauma: a bullet in the larynx - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Penetrating laryngeal traumas due to gunshot wounds are rare cases. These cases are generally encountered during wars. Here, we report a 40-year-old man who presented with a gunshot wound in his neck. Physical and radiological examination revealed a foreign body in the larynx. A piece of bullet was extracted from the right supraglottic part of his larynx via direct laryngoscopy under general anesthesia. The patient had a good recovery without any symptom postoperatively. Early recognition and accurate management of penetrating laryngeal traumas are essential. Establishing a patent airway and a good quality of voice are important aims for long-term results.
Keywords: gunshot wounds; penetrating laryngeal trauma; bullet; MANAGEMENT; INJURY